Effects of paclobutrazol, biochar and water stress on growth of oil palm (Elaeis guineensis Jacq.) seedlings - Hidayat, Taufiq Caesar (2015)
Drought promotes water stress on oil palm seedlings in the main nursery or field. Biochar (BC) could improve soil moisture retention while paclobutrazol (PBZ) could protect plants against water stress during drought period. There is a lack of information on utilization of PBZ and BC and their rates on growth of oil palm seedlings. Experiment 1 was conducted to determine effect of BC and PBZ on growth of oil palm seedlings in main-nursery at the IOPRI Marihat substation, Indonesia. Three months olds DxP-Simalungun seedlings from prenursery were transplanted into polybags filled with soil containing 0, 50 or 100 g BC. After 3 months, seedlings were treated with 95% PBZ at 0, 100, 200 and 300 mg/seedling. At harvest, seedling height, rachis length and frond number were measured monthly. Leaf area, dry shoot and dry root weight, gibberellin (GA) contents and PBZ residue were measured at 12 months. Combination of BC and PBZ increased seedling high significantly by seedling ages, but the rate of increment was not as high as compared to treatment of BC alone. Seedling height increased gradually at 6 to 9 months, followed by a rapid increase from 9 to 12 months. Combination of 50 g BC + 100 mg PBZ produced desired seedling height of 120 cm. PBZ decreased rachis length after it was applied, the effect was reversed over time. The combination of BC and PBZ showed a synergistic effect, promoting or reducing root dry weight. The 50 g BC + 100 mg PBZ promoted seedling dry root weight. BC at 50 g/seedling combined with PBZ at 200-300 mg/seedling decreased root dry weight. GA contents decreased as PBZ application rates were increased. PBZ had a reversed effect on GA. The 50 g BC+100 mg PBZ combination was selected for Experiment 2. Experiment 2 was conducted to determine the effect of water stress on growth performances of oil palm seedling transplants from selected BC and PBZ treatments under simulated field condition. Twelve months old seedlings with 50 g BC + 100 mg PBZ and control were transplanted into polybags. Then, the seedlings were placed under a rain-shelter and exposed to three water stress treatments: 50, 75 and 100 of field capacity (FC). Seedling height, leaf area,leaf chlorophyll contents, photosynthetic and transpiration rates, shoot and root dry weights and leaf proline contents were determined on 13, 14 15 and 16 months old seedlings. The 50 g BC + 100 mg PBZ treated seedlings had smaller leaf area, increasing chlorophyll contents, increased photosynthesis and stimulated transpiration rate compared to control seedlings. Higher proline contents of control seedlings indicated seedlings stress compared to those of treated seedlings. In conclusion, BC produced better seedlings condition while PBZ retards seedling growth by blocking GA synthesis, thus producing compact seedlings. Compact seedlings were easy to maintain and transplant, requiring less transportation space. Thus, it recommended applying seedling with 50 g of BC and 100 mg PBZ per seedling to make it compact and prevent it from drought in the field.